2013
DOI: 10.1186/1550-2783-10-39
|View full text |Cite
|
Sign up to set email alerts
|

Effects of betaine on body composition, performance, and homocysteine thiolactone

Abstract: BackgroundThis study investigated the effects of long term betaine supplementation on body composition, performance, and homocysteine thiolactone (HCTL) in experienced strength trained men.MethodsTwenty-three subjects were matched for training experience (4.8 ± 2.3 years) and body fat percentage (BF%: 16.9 ± 8.0%), randomly assigned to either a placebo (PL; n = 12) or betaine group (BET; n = 11; 2.5 g/day), and completed a 6 week periodized training program consisting of 3 two-week micro-cycles. Bench press an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 40 publications
7
81
5
Order By: Relevance
“…For example, our laboratory (31) and others (4, 13, 22) showed BT supplementation improved select physical performance measures, likely due to its ability to donate methyl groups thereby upregulating creatine synthesis in skeletal muscle (3, 7). This mechanism, however, was recently questioned (8).…”
Section: Introductionmentioning
confidence: 88%
“…For example, our laboratory (31) and others (4, 13, 22) showed BT supplementation improved select physical performance measures, likely due to its ability to donate methyl groups thereby upregulating creatine synthesis in skeletal muscle (3, 7). This mechanism, however, was recently questioned (8).…”
Section: Introductionmentioning
confidence: 88%
“…For the chest, we measured the girth, taken at the level of the middle of the sternum, with the tape passing under the arms and at the end of a normal expiration. For the thigh and arm, we assessed the maximal cross-sectional area (CSA) using the method of Moritani-DeVries, which is based on girth and skin-fold measurements [ 41 – 43 ]. The literature shows that the muscle CSA measures obtained by the Moritani-DeVries method are highly correlated with measures obtained by computer tomography or muscle biopsy, the gold standards for muscle CSA measurement [ 41 – 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Betaine has been suggested as a nutrient that can protect cells and proteins from environmental stress and prevent chronic diseases in humans ( Craig, 2004 ; Patrick, 2002 ). In addition, Cholewa et al (2013) reported that betaine supplementation improved the performance and body composition of strength-trained males. Therefore, it seems likely that increasing the concentrations of l -carnitine and betaine would improve the nutritional value of meat.…”
Section: Introductionmentioning
confidence: 99%